Impaired Cerebral Autoregulation in Parkinson's Disease: An Orthostatic Hypotension Analysis - Xing, Yingqi; Li, Qing; Xu, Erhe; Zeng, Jingrong; Li, Qiuping; Mei, Shanshan; Hua, Yang (Frontiers in Neurology, 2022)
Orthostatic hypotension (OH) is an early non-motor manifestation of Parkinson's disease (PD). However, the underlying mechanism of hemodynamic changes in patients with PD and OH remains unclear. This study aimed to investigate the dynamic cerebral autoregulation changes in patients with PD with OH. Ninety patients with PD and 20 age- and sex-matched healthy controls (HCs) were recruited. The patients' non-invasive blood pressure (BP) and cerebral blood flow velocity were simultaneously recorded at supine and orthostatic positions during the active standing test (AST). Transfer function analysis was used to determine autoregulatory parameters including gain [i.e., damping effect of dynamic cerebral autoregulation (dCA) on the magnitude of BP oscillation] and phase difference (i.e., the time delay of the cerebral blood flow response to BP). Sixteen patients (17.8%) in the PD population were diagnosed with OH (PD-OH). The AST results were normal for 74 patients (82.2%) (PD-NOR). In the supine position, the PD-OH group had a lower phase degree than the PD-NOR group (50.3 ± 23.4 vs. 72.6 ± 32.2 vs. 68.9 ± 12.1, p = 0.020); however, no significant difference was found upon comparing with the HC group. In the orthostatic position, the normalized gain was significantly higher for the symptomatic OH group than for the asymptomatic OH group and HC group (1.50 ± 0.58 vs. 0.97 ± 0.29 vs. 1.10 ± 0.31, p = 0.019). A symptomatic OH in the PD population indicates an impaired cerebral autoregulation ability in the orthostatic position. Cerebral autoregulation tends to be impaired in the supine position in the OH population.